Economic abuse and its associations with symptoms of common mental disorders among women in a cross-sectional survey in informal settlements in Mumbai, India - Suman Kanougiya; Nayreen Daruwalla; Lu Gram; Apoorwa Deepak Gupta; Muthusamy Sivakami; David Osrin (BMC, 2021)
Abstract Background Domestic violence takes a range of interconnected forms, of which economic abuse is common, but less studied than others. We examine the prevalence of economic abuse, its determinants, and its association with symptoms of depression, anxiety, and suicidal ideation. Methods Our cross-sectional survey in informal settlement areas in Mumbai, India, asked women aged 18-49 years 15 questions about acquisition, use, and maintenance of economic resources, demographic and socioeconomic factors, and physical, sexual, and emotional violence. We administered the Patient Health Questionnaire 9 (PHQ-9) and Generalised Anxiety Disorder 7 (GAD-7) scales and asked about suicidal thinking. Determinants of economic abuse and its associations with positive screens for depression and anxiety were explored in univariable and multivariable logistic regression models. Results Of 4906 ever-married women respondents, 23% reported at least one form of economic abuse by either an intimate partner or another family member. The commonest were denial of property rights (10%), not being trusted with money (8%), and coercive appropriation of belongings (7%). Economic abuse was more commonly reported by widowed, separated, or divorced women than by married women (aOR 12.4; 95% CI 6.4, 24.1), and when their partners used alcohol or drugs (aOR 1.4; 95% CI 1.2-1.7). Women had greater odds of reporting economic abuse if they had suffered emotional (aOR 6.3; 95% CI 5.0-7.9), physical (aOR 1.9; 95% CI 1.4-2.6), or sexual violence (aOR 5.4; 95% CI 3.6-8.1) in the preceding 12 months. Economic abuse was independently associated with positive screens for moderate-severe depression (aOR 2.6; 95% CI 2.0-3.4), anxiety (aOR 2.7; 95% CI 1.9-3.8), and suicidal ideation (aOR 2.2; 95% CI 1.5-3.1). The odds of anxiety and depression increased with each additional form of economic abuse. Discussion To our knowledge, this is the first community-based study in India of the prevalence of economic abuse and its associations with symptoms of common mental disorders. It provides empirical support for the idea that economic abuse is at least as harmful to women's mental health as physical violence. Surveys should include questions on economic abuse and prevention and intervention strategies need to help survivors to understand its forms.